Analysis On The Students’ Descriptive Writing In Dual-Degree Program Stikom Bali - I Gusti Agung Vony Purnama (Jurnal Sistem dan Informatika (JSI), 2016)
This study aims to find out the find out the ability of the students’ descriptive writing, and the second aim is to find out the students’ problem in writing a descriptive paragraph by the students of semester 2 year intake 2014 Dual-Degree Program STIKOM Bali in English subject. This study used the theory of English Grammar and theory of writing particularly on the descriptive writing. There was 31 students’ descriptive writing analyzed by using the collecting data method of qualitative. From the data analysis, there were found three students inappropriate descriptive writings. Therefore, it can be concluded that the students’ ability in terms of appropriateness descriptive writing is good. However, in terms of the problems in writing, they have problems in developing the idea of the identification into description, and the other problems were on the management of their writing which was not proper, therefore, their writing were not coherent.